Dynamics of dissolved inorganic nitrogen in a tropical tidal river - Rahman, Mohammad Mustafizur (2016)
Dissolved inorganic nitrogen plays a critical role in controlling primary production in the river ecosystem. A 12-month study (September 2014-August 2015) was conducted to know the spatio-temporal dynamics of inorganic nitrogen in the Kuantan river which is influenced by daily tidal activity. Various forms of inorganic nitrogen (NO2- N, NO3-N and NH3-N) were measured at two sampling sites: 5 (near Kuantan city) and 10 (upstream, freshwater zone) km upstream from the Kuantan river estuary. Each zone had a total of three sampling stations which were considered as replication. Besides inorganic nitrogen, physical parameters such as water temperature, dissolved oxygen (DO), pH, conductivity, salinity were measured. All parameters were measured in the three layers (surface, middle and bottom) of the water column in each sampling station. Results indicated that mean inorganic nitrogen concentration near the Kuantan city (2.25±0.09 mg L-1) was significantly higher than the mean inorganic nitrogen concentration in the upstream zone (1.46±0.11 mg L-1). This might be due to organic discharge into the river from the Kuantan city compare to upstream zone. Similar pattern of inorganic nitrogen concentration was also observed in the case salinity, conductivity and DO concentrations. Overall inorganic nitrogen content was higher near the bottom water (2.15±0.16) compare to surface (1.65±0.10) and middle (1.75±0.12) layers of water. Both temperature and dissolved oxygen concentration were higher in the surface water compare to middle and bottom layers of water. The mean highest and lowest inorganic nitrogen concentrations were observed in January (0.70±0.15) and May (3.46±0.25), respectively. The overall mean inorganic nitrogen concentrations were lower in the monsoon months compare to non-monsoon months.